2020
DOI: 10.3390/w12082271
|View full text |Cite
|
Sign up to set email alerts
|

Flood Evacuation Routes Based on Spatiotemporal Inundation Risk Assessment

Abstract: For flood risk assessment, it is necessary to quantify the uncertainty of spatiotemporal changes in floods by analyzing space and time simultaneously. This study designed and tested a methodology for the designation of evacuation routes that takes into account spatial and temporal inundation and tested the methodology by applying it to a flood-prone area of Seoul, Korea. For flood prediction, the non-linear auto-regressive with exogenous inputs neural network was utilized, and the geographic information system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Commonly used ML algorithms were summarized by Mosavi et al [4], and they include Artificial Neural Networks (ANN) and MultiLayer Perceptron (MLP) [5], Adaptive Neuro-Fuzzy Inference System (ANFIS) [6], Wavelet Neural Networks (WNN) [7], Support Vector Machine (SVM) [8], Decision Tree (DT) [9], and hybrid models [10,11]. More recently, advanced methods such as deep learning (e.g., Convolutional Neural Networks (CNN) [12,13]), Extreme Machine Learning (EML) [14], dynamic or recurrent neural networks (e.g., Nonlinear Autoregressive network with exogenous inputs (NARX) [15,16], and Long Short-Term Memory (LSTM) [17]) are also gaining popularity in the hydrological field.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used ML algorithms were summarized by Mosavi et al [4], and they include Artificial Neural Networks (ANN) and MultiLayer Perceptron (MLP) [5], Adaptive Neuro-Fuzzy Inference System (ANFIS) [6], Wavelet Neural Networks (WNN) [7], Support Vector Machine (SVM) [8], Decision Tree (DT) [9], and hybrid models [10,11]. More recently, advanced methods such as deep learning (e.g., Convolutional Neural Networks (CNN) [12,13]), Extreme Machine Learning (EML) [14], dynamic or recurrent neural networks (e.g., Nonlinear Autoregressive network with exogenous inputs (NARX) [15,16], and Long Short-Term Memory (LSTM) [17]) are also gaining popularity in the hydrological field.…”
Section: Introductionmentioning
confidence: 99%
“…The specific evacuation routes of the closest shelters to each population grid were identified and visualized by a limiting condition of 3 km. This step is meaningful since it has been revealed that the residents in Syracuse have no sense of where to go during a flood event [28]. Therefore, the results from this study indicate the nearest designated evacuation shelter and evacuation route.…”
Section: Flood Evacuation Designmentioning
confidence: 81%
“…Many scholars have studied the death rate of floods using inundation depth. Literature suggests that the death rate of a population is strongly related to the inundation depth [28]. This study produced an estimate of the loss of population based on the death rate and inundation depth determined using the equation expressed in Figure 7.…”
Section: Loss Of Population In a 500-year Flood Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite forecasts of cloud covers - [2] easily provide an indication of the spatial extent of cloudy regions over a city, and meteorological forecasts of extreme weather events, including a forecast of heavy precipitation, are also possible from observational and modelling studies. Models rely on the successful prediction of the onset times of precipitation for better flood management, and any evacuation measure is invariably tied down to the time duration over which the precipitation event occurs [3][4][5]. Earlier studies have highlighted that precipitation onset times as well as the initial storage levels in local water tanks are crucial parameters that modulate the extent of flooding in a region [6].…”
Section: Introductionmentioning
confidence: 99%